Hydrated electron dynamics: from clusters to bulk - Bragg, A.E.; Verlet, J.R.R.; Kammrath, A.; Cheshnovsky, O.; Neumark, D.M. (Science, 2004)
The electronic relaxation dynamics of size-selected (H2O)n–/(D2O)n[25 n 50] clusters have been studied with time-resolved photoelectron imaging. The excess electron () was excited through the transition with an ultrafast laser pulse, with subsequent evolution of the excited state monitored with photodetachment and photoelectron imaging. All clusters exhibited p-state population decay with concomitant s-state repopulation (internal conversion) on time scales ranging from 180 to 130 femtoseconds for (H2O)n– and 400 to 225 femtoseconds for (D2O)n–; the lifetimes decrease with increasing cluster sizes. Our results support the "nonadiabatic relaxation" mechanism for the bulk hydrated electron (), which invokes a 50-femtosecond internal conversion lifetime.